The COVID-19 pandemic and Poland’s macroeconomic situation - Paulina Pukin-Sowul (Malopolska School of Economics in Tarnow, Poland, 2021)
TThe research objective was to evaluate the impact of the COVID-19 pandemic on the macroeconomic situation in Poland. The research employed critical analysis of scientific literature and an analysis of statistical data. The first part of the article describes the channels through which the COVID-19 pandemic affects economy. The second part contains an analysis of changes in the mood of entrepreneurs, using monthly fluctuations of the indices measuring economic situation and consumer confidence, followed by an evaluation of Poland’s macroeconomic situation in the context of the developing COVID-19 pandemic. This evaluation was based on an analysis of quarterly data concerning changes in the GDP and its component parts, the labour market situation and changes in price indices from the first quarter of 2018 to the second quarter of 2021. The research results showed that the COVID -19 pandemic and the restrictions imposed by the Polish government caused negative consequences in the Polish economy. This is evidenced by the worse mood prevalent among entrepreneurs and consumers. Over the time period analysed, the macroeconomic situation of Poland was observed to have deteriorated as well, with the decreased rate of economic growth, higher unemployment rate and accelerated inflation processes.